Perwujudan Representational Meaning Kim Shin Kwan Kong di Klenteng Hok An Kiong Surabaya - Hendry Sugiharto; Andereas Pandu Setiawan (Intra, 2013)
Hok An Kiong chinese temple is the Tri Dharma’s place of worship in Surabaya city, East Java. The research was conducted at Kwan Kong god statue and interior elements contained in the temple’s main altar hall. This interior hall was designed by Fujian (Southern China) culture style and has been constructed since 1821 that are rich of original Chinese cultural values and historical values. The process of analysis using the iconography method by van Leeuwen, the purpose of this method is to determine the meaning of Kwan Kong god statue with first layer. The main function of Kwan Kong god statue physicaly as the worship orientation for the temple’s worshipers, but by iconography method shows the impact who manifested in some of the interior elements in the temple’s main altar hall.